Reduction of Flocculation in Potato-Based Milk Analogues - Kwon,Seohyun (2025)
This study investigates the mechanisms driving flocculation in potato-based milk analogues, a critical quality defect arising during long-term storage. Initial hypotheses implicated starch retrogradation as the primary destabilization mechanism, given its well-documented role in plant-based systems. However, enzymatic treatment with α-amylase successfully hydrolyzed amylose (confirmed via iodine staining) and reduced viscosity, but failed to prevent aggregation, therefore excluding starch recrystallization as the dominant factor. Comparative analysis with potato-based cooking cream, which exhibited no flocculation despite higher fat content (13% vs. 3% in milk), provided another assumption. Potato milk’s higher protein-to-fat ratio (0.528 vs. 0.085 in cream) promotes protein-protein bridging and network formation. Combining the findings from SAXS/WAXS, centrifugation, and microscopy helped us understand the main reasons behind flocculation in potato milk analogues. SAXS/WAXS data demonstrated no detectable retrogradation-induced crystallinity in flocs, which indicated that starch wasn't the primary reason for flocculation. TD-NMR data showed non-enzyme treated samples centrifuged bottom had very low mobile water compared to the top phase, and enzyme-treated samples showed no bottom phase, which indicates the removal of starch structures. However, the top phase of milk persisted. Microscopy images of both enzyme-treated and non-enzyme-treated potato milk analogues revealed similar oil droplet distributions, with no clear evidence of major aggregation in either group after 150 days of storage. Occasional small clusters were observed, but overall, both types of milk showed comparable results, suggesting that enzymatic treatment did not significantly alter the droplet morphology or reduce flocculation compared to non-enzyme-treated samples. In sharp contrast, cooking cream displayed uniformly dispersed oil droplets without visible aggregation, regardless of storage conditions, confirming its superior emulsion stability. Instead, protein-driven aggregation was suggested as the dominant factor: excess pea protein formed interfacial bridges between fat droplets, as evidenced by persistent surface flocs in centrifuged enzyme-treated samples. In contrast, cooking cream exhibited exceptional stability across all conditions, maintaining uniform droplet dispersion (D(0.9) smaller than 5 µm, while the potato milk analogue showed bigger than 15 µm after 130 days. The stability difference was attributed to cooking cream’s optimized protein-to-fat ratio (0.085 vs. 0.528 in milk), which minimized interfacial overcrowding and prevented bridging. These findings collectively shift the focus from starch modification to protein-oil balance as the critical lever for improving potato milk stability. Enzymatic starch hydrolysis reduced viscosity but did not address protein overcrowding at the oil-water interface, as evidenced by persistent surface flocs in centrifuged enzyme-treated samples. As a conclusion, the results focus on protein-oil ratio optimization as a key way to control milk quality. Reducing pea protein content is expected to mitigate bridging without compromising emulsification.
Keywords: food engineering nutrition and food chemistry; flocculation; potato-based milk analogues; plant-based milk; emulsion stability; protein-to-fat ratio; pea protein; starch retrogradation; emulsification; particle size distribution; protein bridging; shelf life; product quality; food engineering; storage conditon; viscosity; microscopy; NMR; SAXS; WAXS